(untitled) (BIRDEM Medical Journal, 2019)
A 57-year-old male patient of chronic kidney disease on maintenance hemodialysis via right radio-cephalic fistula presented with swelling of his right arm and right half of face and headache. With the clinical suspicion of central venous obstruction he underwent venogram of right upper limb. A stenosis was found in right brachiocephalic vein. He underwent a percutaneous transluminal balloon angioplasty and his symptoms improved substantially. Birdem Med J 2019; 9(1): 82-84